Química computacional no ensino do conceito de orbital atômico: uma revisão sistemática da literatura - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2026)
Quantum Theory is recognized as the most successful theory in all human science; however, many conditions resulting from its application are still little explored in high school chemistry classrooms and even in undergraduate studies. Based on this premise, this work aims to develop a theoretical-analytical study through a literature review and epistemological analysis. Therefore, it aims to measure the contribution of computational chemistry to chemistry teaching, where through the Quantum Study of the Atomic Orbital from the perspective of Computational Chemistry, the integration between Quantum Theory, Scientific Modeling, and Chemistry teaching will be analyzed. The study aims to theoretically ground the use of computational methods such as Hartree–Fock and Density Functional Theory as tools for mediating the learning of the atomic orbital concept. The results indicate that computational visualization can reduce epistemological obstacles and foster meaningful learning of the quantum model.
Keywords: Estudo Quântico; Química computacional; Ensino de Química; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::QUIMICA TEORICA; ODS 4 – Educação de qualidade; ODS 9 – Indústria, inovação e infraestrutura; ODS 10 – Redução das desigualdades